HARMONISATION AND LEGAL CHALLENGES OF AGREEMENTS IN INDONESIA: STRENGTHENING ENVIRONMENTAL PROTECTION, GLOBAL RESOURCE MANAGEMENT, AND DIGITAL ADAPTATION IN THE CONTEXT OF NATIONAL AND INTERNATIONAL LEGAL SYNCHRONISATION – A LITERATURE REVIEW - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
This study examines the harmonisation and challenges faced by treaty law in Indonesia in two main areas, namely environmental protection and global resource management, as well as the adaptation of treaty law in the digital era. Using a systematic literature review method, this study analyses various national and international legal instruments that play a role in synergising Indonesian legal regulations with global standards. The results of the study show that there are gaps in implementation and regulation that have resulted in suboptimal environmental protection and resource management, as well as digital law adaptation still facing regulatory and law enforcement obstacles. The study recommends the need for responsive regulatory revisions, institutional strengthening, and active legal diplomacy to ensure effective synchronisation of national and international laws for the sake of sustainable development and Indonesia's legal competitiveness in the global arena.